Valores associados à compra de automóvel por jovens no Ceará: um estudo sob a ótica da cadeia de meios-fim - Nunes, Natália de Sena (2010)
The companies see the growing importance of the customer to the market, a customer is demanding more and more and realize that the choices the market offers, especially when it comes to the automotive sector. This sector faces a competitive environment and therefore need to implement strategies of differentiation for the consumer to prefer one company over the other. To achieve your goal, organizations must develop strategies which can be done by segregating the targeted market, an important segment to be worked on is the youth segment, which has needs and desires to be met, who are major influencers at home and whose dream of consumption is: the automobile. To capture this audience, however, we should try to understand what motivates them to buy a vehicle, what are the values behind the purchase of a particular car, for the company to offer the product that the customer demand. This is, then, the goal of this research. Therefore, it is necessary a study that goes beyond the superficiality, a qualitative research. This research is analyzed from the perspective of the Means-End Chain Theory, so important for the identification of attributes, consequences and values involved in the relationship between the young and the car. And to achieve the objectives of this study it was used the method of in-depth interviews through the laddering technique. The survey was conducted on a sample of 30 young people in Ceará between 18 and 24 who have their own cars and have chosen their vehicle at the time of purchase. The interviews took place from October to December 2009. The results indicate the predominance of individualistic field from the perspective of Schwartz, where the core values highlighted were: well-being (feeling well), safety, enjoyment, worry about the future and quality of life.